A Review on Improving Thermal-Hydraulic Performance of Finand- Tube Heat Exchangers - Nickolas, N.; Moorthy, P.; A. N., Oumer; M., Ishak (IOP Publishing, 2017)
Fin-and-tube heat exchangers are one of the most common type of heat exchangers that are normally used in sectors that require small size and light weight but high heat transfer capabilities. Compact fin-and-tube heat exchangers experiences high convective thermal resistance at the air-side due to the thermo-physical properties of air. Thus, the purpose of this paper is to provide an overview of research works that are relevant to improving thermalhydraulic performance at the air-side of fin-and-tube heat exchangers. This paper covers a variety of parameters such as tube parameters like tube arrangement, tube shapes and tube inclination angles; extended surfaces such as different shapes of fins and different parameters of vortex generators like attack angles, shapes and locations. Overall, for most modifications there was increment in heat transfer but accompanied with a pressure drop penalty. However, this varies for different combinations of parameters thus this review is to help understand how every mentioned parameters influences the thermal-hydraulic performance.